2014
DOI: 10.1111/bjh.13202
|View full text |Cite
|
Sign up to set email alerts
|

Factors predicting survival in peripheral T‐cell lymphoma in the USA: a population‐based analysis of 8802 patients in the modern era

Abstract: SummaryCurrent prognostic models for peripheral T-cell lymphoma (PTCL) have multiple limitations, and questions exist regarding applicability to current patients. We utilized the Surveillance Epidemiology and End Results (SEER)-18 database to evaluate factors affecting overall survival (OS) of PTCL in the modern era and identified 8802 patients between 2000-2010. Most subtypes of PTCL increased in incidence during the study period. In univariate analyses, age >55 years, black race, advanced stage, absence of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
2
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 38 publications
1
21
2
2
Order By: Relevance
“…CHOP is the standard therapy for PTCL ( 51) although new drugs (pralatrexate and romidepsin) received approval in 2009 ( 52, 53). Survival is generally described as poor, although our cancer-specific survival estimate of approximately 65% for PTCL was higher than previously suggested ( 54, 55). We find that 5-year cancer-specific survival for the PTCL cases not otherwise specified was 40%, similar to what is reported in the literature (54, 55).…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…CHOP is the standard therapy for PTCL ( 51) although new drugs (pralatrexate and romidepsin) received approval in 2009 ( 52, 53). Survival is generally described as poor, although our cancer-specific survival estimate of approximately 65% for PTCL was higher than previously suggested ( 54, 55). We find that 5-year cancer-specific survival for the PTCL cases not otherwise specified was 40%, similar to what is reported in the literature (54, 55).…”
Section: Discussioncontrasting
confidence: 86%
“…Survival is generally described as poor, although our cancer-specific survival estimate of approximately 65% for PTCL was higher than previously suggested ( 54, 55). We find that 5-year cancer-specific survival for the PTCL cases not otherwise specified was 40%, similar to what is reported in the literature (54, 55). Our PTCL classification does include Alk+ T-cell lymphoma, and this also has a low survival rate (5-year survival 52%).…”
Section: Discussioncontrasting
confidence: 86%
“…A SEER (Surveillance and Epidemiology End Results) database analysis from 1992 to 2009 showed that, with the exception of ALCL, the incidence of common PTCL subtypes has greatly increased over the past few decades (the combined rate more than tripled from 1992 to 2009) [25]. However, over this same time period, survival times did not increase [25] as they have for patients with B-cell lymphoma [26].…”
Section: Discussionmentioning
confidence: 99%
“…However, over this same time period, survival times did not increase [25] as they have for patients with B-cell lymphoma [26]. Despite poor outcomes, anthracycline-based regimens continue to be commonly used for the treatment of PTCL [1-3,8-11].…”
Section: Discussionmentioning
confidence: 99%
“…No que se refere à distribuição dos casos por variante histopatológica, assim como demonstrado por outros autores em projetos cooperativos internacionais (International T-cell Lymphoma Project, 2008;FOSS et al, 2011;PETRICH et al, 2014), no presente estudo, prevaleceu o subtipo LCTP/SOE que ocorreu em 34,9% A imunoexpressão da proteína ALK1 é classicamente considerada como variante associada a bom prognóstico, de forma independente no LGCA (GAYSCONE et al, 1999;ten BERGE et al, 2000). Entretanto, estudos recentes demonstraram resultados contraditórios.…”
Section: Características Clínico-laboratoriais E Epidemiológicasunclassified